Tourism for whomn - Velez, Jose Mari. (Quezon City GMA Radio Television News and Public Affairs)
Advertises tourist soots in the Philippines in order to promote domestic tourism. Identifies and addresses the problem of the trade.
VHS.
Host, Jose Mari Velez.
Keywords: Tourist trade -- Philippines